Dasycladalean algae from the Norian-Rhaetian reef carbonates of Argoli Peninsula, Greece - Senowbari-Daryan, Baba (Acta Palaeontologica Romaniae, 2014)
Three new dasycladales algae, including Probolocuspis sarmeikensis nov. sp. Probolocuspis? tenuipora nov. sp. and Diplopora obliguspora nov. sp. are described from Mavrovouni Mountains (Argolis Peninsula, Greece). The specimens were found embedded in micritic sediments between the reef builders in the Norian-Rhaetian reef carbonates near the town of Sarmeika. The genus Probolocuspis was known from the Ladinian-Carnian of Iran and the Alps. Argolis Peninsula is the third locality, where this genus was found. The stratigraphic range of the genus should be extended from Ladinian to Norian (perhaps to Rhaetian?).
UnivIS-Import:2017-11-07:Pub.2014.nat.dgeo.IGM.LP.dasycl
Keywords: Dasycladales; Probolocuspis; Diplopor; Norian; Rhaetian reef; Argolis; Greece